معالم البناء السياسي عند ابن عاشور من خلال تفسيره التحرير والتنوير: دراسة موضوعية - Hocini, Mohamed Amine (Borneo International Journal of Islamic Studies, 2023)
يهدف هذا البحث إلى بيان معالم البناء السياسي عند ابن عاشور في تفسيره التحرير والتنوير من خلال دراسة موضوعية، تتمثل إشكالية البحث في أنّ حديث القرآن الكريم عن معالم البناء السياسي جاء متفرّقا في آياته وسوره؛ فلذلك كان الوقوف على التصوّر الشامل لتلك المعالم يشوبه شيء من الصعوبة؛ وبالتالي كانت الحاجة ملّحة إلى استقراء القرآن الكريم لتحديد معالم البناء السياسي عند ابن عاشور وتقديمها بشكل واضح ومتكامل كما أرادها القرآن الكريم. تتجلى أهمية هذا البحث في أنه يُعنى ببيان معالم البناء السياسي -الذي هو أحد أهم مرتكزات البناء الحضاري- في ضوء النظرة القرآنية وآليات بنائها، وهو موضوع تحتاجه الأمة بشكلٍ كبير في ظلّ التراجع الذي تعيشه منذ زمن. سيعتمد البحث المنهج الاستقرائي وذلك بتتبع الآيات القرآنية ذات الصلة وتفسير ابن عاشور لها ثم تحليلها بالاستعانة ببعض المصادر والمراجع ذات الصّلة. توصل البحث إلى أنّ نظام قوام الأمة السياسي في ضوء القرآن الكريم يتمثل في مبدأ الحكم بالعدل الذي هو واجب ولاة الأمور، ومبدأ السمع والطاعة التي هي واجب الرّعية، ومبدأ الشورى، وأنّ مدار السياسة والغاية منها درءُ المفاسد وجلب المصالح. This research aims to clarify the milestones of political development according to Ibn ‘Āshūr in his interpretation of al-Taḥrīr wa Tanwīr through a thematic study. The problem with the research is that the Holy Qur'an's discussion of the milestones of developing politics is dispersed throughout its verses and chapters; therefore, acquiring a comprehensive understanding of those milestones was somewhat difficult. Thus, there was an urgent need to extrapolate the Holy Qur’ān to determine the milestones of political development according to Ibn ‘Āshūr and to present them in a clear and integrated manner. The importance of this research is evident in that it is concerned with showing the milestones of political development - which is one of the most important pillars of civilization development - in the light of the Qur’ānic view, and it is a subject that the nation greatly needs considering the decline it has been experiencing for a long time. The research will adopt the inductive approach by following the relevant Qur’ānic verses and Ibn ‘Āshūr 's interpretation of those verses, and then analysing them with the help of some relevant sources and references. The research concluded that the political system of the nation’s strength in the light of the Holy Qur’ān is represented in the principle of ruling with justice, which is the duty of rulers, the principle of obedience, which is the duty of the people, and the principle of ShËrā. Finally, politics and its purpose aim to ward off evil and bring interests (Jalb al-Maṣāliḥ wa dar’ al-Mafāsid).